Adolescent predisposition to binge drinking is associated with differences in inhibitory control MEG event-related fields - Antón-Toro, Luis Fernando; Shpakivska-Bilan, Danylyna; López-Abad, Lucía; Del Cerro-León, Alberto; Uceta, Marcos; Bruña, Ricardo; García-Moreno, Luis M.; Maestú, Fernando (Frontiers in Psychiatry, 2026)
IntroductionAdolescent binge drinking (BD) is a major public health concern, yet little is known about the neural markers that precede alcohol initiation. This longitudinal study examined whether magnetoencephalography (MEG) event-related fields (ERFs) recorded during inhibitory control predict later BD. MethodsEighty-one alcoholnaïve adolescents initially completed a Go/No-Go task during MEG acquisition, alongside self-report measures of impulsivity, sensation seeking, and executive functioning. After two years, 44 participants remained eligible and were classified as controls (CN, n = 20; 10 females) or binge drinkers (BD, n = 24; 12 females) based on reported habits of alcohol consumption. ResultsBehavioral analyses showed no group differences in accuracy in the inhibition task, impulsivity (BIS-11), or executive functioning (BRIEF-SR). The BD group reported higher sensation seeking (SSS-V). When studying electrophysiological activity, cluster-based permutation analyses revealed significant group differences in both the M200 (180–260ms) and M300 (310–510ms) components. In both cases, BD adolescents exhibited larger amplitudes, with sensors localized to left medial and dorsolateral prefrontal areas. These differences were moderate predictors in logistic regression models. Association between ERF and future alcohol use were not influenced by biological sex. DiscussionThe results converge with prior evidence of left prefrontal hyperactivation in adolescent BD and developmental studies showing enhanced recruitment of control networks during adolescence. Findings support the hypothesis that atypical prefrontal executive engagement may represent a vulnerability profile that precedes alcohol use and may contribute to the emergence of BD.